2017
DOI: 10.1007/s00221-017-5134-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical perturbations can elicit triggered reactions in the absence of a startle response

Abstract: Perturbations delivered to the upper limbs elicit reflexive responses in stretched muscle at short- (M1: 25-50 ms) and long- (M2: 50-100 ms) latencies. When presented in a simple reaction time (RT) task, the perturbation can also elicit a preprogrammed voluntary response at a latency (< 100 ms) that overlaps the M2 response. This early appearance of the voluntary response following a proprioceptive stimulus causing muscle stretch is called a triggered reaction. Recent work has demonstrated that a perturbation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It is also known that spinal excitability, as tested through the H-reflex, increases ~25 ms prior to the onset of a voluntary response (MacKinnon and Rothwell, 2000). Given that the fastest voluntary RTs in a compensate task occur during the R3 epoch (Forgaard et al, 2018), the generic R2 increase we have observed on trials with a voluntary response may have resulted from descending modulation of spinal excitability preceding the voluntary response. This mechanism could explain why the R1 response can be facilitated when the voluntary response is temporally cued to occur earlier (Lewis et al, 2006), and why the LLR does not modulate if onset of the voluntary response occurs far beyond the end of this stretch response (Manning et al, 2012).…”
Section: Volition and Llr Facilitationmentioning
confidence: 67%
“…It is also known that spinal excitability, as tested through the H-reflex, increases ~25 ms prior to the onset of a voluntary response (MacKinnon and Rothwell, 2000). Given that the fastest voluntary RTs in a compensate task occur during the R3 epoch (Forgaard et al, 2018), the generic R2 increase we have observed on trials with a voluntary response may have resulted from descending modulation of spinal excitability preceding the voluntary response. This mechanism could explain why the R1 response can be facilitated when the voluntary response is temporally cued to occur earlier (Lewis et al, 2006), and why the LLR does not modulate if onset of the voluntary response occurs far beyond the end of this stretch response (Manning et al, 2012).…”
Section: Volition and Llr Facilitationmentioning
confidence: 67%
“…EMG activity related to WE was recorded from right extensor carpi radialis muscle (ECR). As the IS can be a source of a startle reaction, surface EMG activity was recorded from the right orbicularis oculi (OOc) and sternocleidomastoid muscles (SCM), which are considered “startle indicator muscles” (Carlsen et al 2011 ; Forgaard et al 2018 ). Filter settings were 10–10,000 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Current evidence suggests that the RST is responsible for the increase in the LLR when participants are instructed to resist a perturbation rather than yield (3). Additionally, the StartReact experimental paradigm has shown to elicit a faster than normal planned voluntary EMG response ( ∼ 70 ms post perturbation onset) in the presence of a startling acoustic stimulus prior to a perturbation (19, 20). The decrease in the voluntary response latency is likely contributed by the RST as the only supraspinal pathway able to act with such a short response time (21, 19, 16).…”
Section: Introductionmentioning
confidence: 99%